Can Screening and Confirmatory Testing in the Management of Patients with Primary Aldosteronism be Improved? - Stowasser, Michael; Ahmed, Ashraf; Guo, Zeng; Wolley, Martin; Ungerer, Jacobus; McWhinney, Brett; Poglitsch, Marko; Gordon, Richard (Hormone and Metabolic Research, 2017)
Widespread application of the plasma aldosterone/renin ratio (ARR) as a screening test has led to the recognition that primary aldosteronism (PA) is the most common specifically treatable and potentially curable form of hypertension, accounting for 5–10% of patients. Maximal detection requires accurate diagnostic approaches and awareness and control of factors that confound results, including most antihypertensives, posture, time of day, dietary salt, and plasma potassium. Recent studies have revealed potential for false positives in patients on beta-adrenoceptor blockers, and, when direct renin concentration (but not plasma renin activity) is used to measure renin, in women during the luteal phase of the menstrual cycle or receiving estrogen-containing contraceptives or hormonal replacement therapy. In addition to verapamil slow release, hydralazine and prazosin, moxonidine has minimal effects on the ARR and can be used to control hypertension during work-up. Fludrocortisone suppression testing, while probably the most reliable means of definitively confirming or excluding PA, is time consuming and expensive, requiring a five day inpatient stay. A novel approach, upright (seated) saline infusion suppression testing (SST), has shown excellent reliability with much greater sensitivity than conventional recumbent SST in a recent pilot study, and requires only a day visit. Accurate measurement of aldosterone is essential for each step of PA workup: introduction of new, highly reliable high-throughput mass spectrometric methods into clinical practice has represented a major advance. In response to concerns raised about accuracy of renin assays, new mass spectrometric methods for measuring angiotensin II are currently being assessed in the clinical setting.
Keywords: primary aldosteronism; screening; confirmatory testing